Factors Affecting the Business Development of Women with Disabilities in Indonesia - Akhmad, Khabib Alia; Santoso, Tri Joko (The Center for Disability Studies and Services Brawijaya University, 2023)
The existence of Micro, Small and Medium Enterprises (MSMEs) in Indonesia has had a significant impact on the nation's economy. Various types of MSMEs have been developed, including MSMEs with disabilities, especially those who are female. This study was conducted to determine the factors that influence the development of women's MSMEs, especially those with disabilities. The research method used was descriptive and qualitative. Data were collected through in-depth interviews, observations, structured interviews, and FGDs. The results show that there are several factors that influence the development of MSMEs for women with disabilities, namely physical accessibility and information, education and training, social support and networks, access to capital and funding, inclusion policies and legal protection, and awareness and attitude change. In addition, internal factors originating from female MSME actors with disabilities, and external factors originating from family, community, and government also influence the development of women with MSMEs with disabilities.